Comparison of Fluoxetine (20 Mg) and Amitriptyline (12.5 Mg) As Adjuvants for The Combination of Paracetamol and Morphine in Cancer Patients' Pain Relief - Ramud, Samawi Husein; Hamdi, Tasrif; Bangun, Chrismas Gideon; Yunanda, Yuki (JAI (Jurnal Anestesiologi Indonesia), 2025)
Background: Pain is one of the most common symptoms in cancer which affects 30–50% of patients on average and rises to 70–90% in cases of advanced disease. As cancer advances, so does the frequency of discomfort associated with the illness. When cancer is detected in its terminal stage, 30–40% of patients report experiencing moderate pain, and 60–100% report experiencing severe pain. Tricyclic antidepressants (TCAs), selective serotonin and norepinephrine reuptake inhibitors (SNRIs), selective serotonin reuptake inhibitors (SSRIs), and monoamine oxidase inhibitors (MAOIs) are the four families of antidepressant medications that have been investigated for use in the treatment of neuropathic pain.Objective: This research was conducted at the pain clinic of Adam Malik Hospital, this study intends to compare the effectiveness of fluoxetine with amitriptyline as an adjuvant to the combination of paracetamol and morphine in reducing pain symptoms in cancer patients.Methods: This study was designed as a randomized, double-blind clinical experiment. The study was carried out in 2023 between July and September. Two groups of forty research participants receiving outpatient care at the pain clinic were formed. Fluoxetine, morphine, and paracetamol were administered to group A (n = 20), whereas amitriptyline, morphine, and paracetamol were administered to group B (n = 20). PainDETECT was used to measure the subjects' pain scores. Both univariate and bivariate data analysis was done. The Chi-Square test, Independent T-test, Paired T-test, and Mann-Whitney were used to examine the bivariate data.Result: The delivery of amitriptyline and fluoxetine resulted in a substantial reduction in PainDETECT scores, with a p-value of less than 0.05.Conclusion: This study show that PainDETECT score was statistically reduced in both the fluoxetine and amitriptyline groups but the reduction was not clinically meaningful because the target score drop was less than 4 on a scale of 0–10, or a 50% reduction in pain.